2019
DOI: 10.17576/jsm-2019-4810-09
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Water Quality Parameters, Growth and Proximate Composition of Juvenile Crab, Portunus pelagicus Cultured in RAS and Non RAS System

Abstract: Juvenile blue swimming crab, Portunus pelagicus were reared over 31 days in two different systems namely recirculating aquaculture system (RAS) and conventional aquaculture system (CAS) to evaluate the water quality parameters, growth, and its body composition. The juvenile crab, weighing of 0.95 ± 0.18 g and stocking was at 40 crabs m -2 and fed twice per day with a commercial shrimp pellet. During the experimental time, significantly (P <0.05) increment in dissolved oxygen (DO) (6.42 ± 0.13), low level of am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Furthermore, the proportion of operational taxonomic units of nitrifying bacteria in the bioreactor decreases significantly when the DO content decreases, especially the growth of heterotrophic nitrifying bacteria that is severely inhibited (Wei, Bi, et al, 2019), while the increase in the DO content (above 5 mg/L) is beneficial to the removal of ammonia, nitrate, and total nitrogen (Luo et al, 2014; Wei, Bi, et al, 2019). Kohinoor et al (2019) compared the growth performance of crabs, Portunus pelagicus , in RAS and non‐RAS systems, and the results showed that the crabs had a higher growth rate in RAS aquaculture ponds because of higher DO and lower ammonia and nitrite content. Meanwhile, the DO content should not be too high: excessive DO at a long time will lead to fish bubble disease whose symptoms include dyspnea, bulging eyes, anemia, and even death, especially causing severe harm to eggs and young fish (Wei, Jiao, et al, 2019).…”
Section: Effects Of Environmental Factors On Rasmentioning
confidence: 99%
“…Furthermore, the proportion of operational taxonomic units of nitrifying bacteria in the bioreactor decreases significantly when the DO content decreases, especially the growth of heterotrophic nitrifying bacteria that is severely inhibited (Wei, Bi, et al, 2019), while the increase in the DO content (above 5 mg/L) is beneficial to the removal of ammonia, nitrate, and total nitrogen (Luo et al, 2014; Wei, Bi, et al, 2019). Kohinoor et al (2019) compared the growth performance of crabs, Portunus pelagicus , in RAS and non‐RAS systems, and the results showed that the crabs had a higher growth rate in RAS aquaculture ponds because of higher DO and lower ammonia and nitrite content. Meanwhile, the DO content should not be too high: excessive DO at a long time will lead to fish bubble disease whose symptoms include dyspnea, bulging eyes, anemia, and even death, especially causing severe harm to eggs and young fish (Wei, Jiao, et al, 2019).…”
Section: Effects Of Environmental Factors On Rasmentioning
confidence: 99%
“…The pressure on blue swimming crab resources must be resolved, considering the dependence on natural stocks in the wild. Kohinoor et al (2019) showed that the survival rate for crab hatcheries was still shallow, with a proportion of only 40.10%. The efforts to manage fishing activities are an alternative that is usually applied by the local government, such as regulations on minimum carapace width, prohibition on catching female swimming crabs, and recommendations for using environmentally friendly fishing gear (Ernawati et al, 2015).…”
Section: Introductionmentioning
confidence: 99%